IDENTIFIKASI KOMPONEN SENYAWA VOLATIL DALAM CUKA BAMBU (BAMBOO VINEGAR) YANG DIPRODUKSI MELALUI PROSES PIROLISIS DI PT. HANAN ALAM LESTARI (MITRA BINAAN CSR PT. BUKIT ASAM Tbk) - Oktaf Rina; Rizka Novi Sesanti; Dedi Teguh; Yeni Ria Wulandari; Hamdani Hamdani; Aang Haryadi (Jurnal Inovasi Penelitian, 2021)
This study aims to identify volatile chemical components in bamboo vinegar (vinegar bamboo) produced by pyrolysis by PT. Hanan Alam Lestari (Guided Partner of PT. Bukit Asam Tbk). The raw material used is bamboo processing waste in the form of bamboo powder and pieces by pyrolysis process at a temperature of 300-450oC. The chemical compounds were analyzed using the Gas chromatography-mass spectroscopy (GC-MS) method at the Laboratory of Research and Development of Forest Products, Bogor. Specifications of tools used to investigate gas or liquid component products using a capillary column (Aglient HP-5MS length 30 m, diameter 250 m, film thickness 0.25 m). By holding the oven temperature at 50°C for 5 minutes, increasing at 5°C/min to 300°C, holding there for 60 minutes and helium as carrier gas. The results of the analysis showed that there were 15 components of volatile compounds and several dominant compounds in bamboo vinegar, namely acetic acid 31.28%; phenol 2-methoxy-guaiocol (12.95%); carbamic acid (11.23%); 2-heptanamine (6.75%) and phenol 4-methoxy-p-cresol (5.56%). The compound components in bamboo vinegar are thought to have antioxidant, antimicrobial and specific color and flavor-forming properties. Several chemical components detected in bamboo vinegar are recommended for use in agriculture as biofungicides and inhibitor compounds.